2016
DOI: 10.1213/ane.0000000000001184
|View full text |Cite
|
Sign up to set email alerts
|

Head-Elevated Patient Positioning Decreases Complications of Emergent Tracheal Intubation in the Ward and Intensive Care Unit

Abstract: Placing patients in a back-up head-elevated position, compared with supine position, during emergency tracheal intubation was associated with a reduced odds of airway-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…In addition to potentially affecting intubation difficulty, some have suggested that an upright position might have other clinically important benefits, such as decreasing risk of aspiration [13]. A recent study of emergent intubations in the ward and ICU settings found lower rates of complications, including aspiration, hypoxemia, and esophageal intubation, when intubating in the upright compared to the supine positions [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to potentially affecting intubation difficulty, some have suggested that an upright position might have other clinically important benefits, such as decreasing risk of aspiration [13]. A recent study of emergent intubations in the ward and ICU settings found lower rates of complications, including aspiration, hypoxemia, and esophageal intubation, when intubating in the upright compared to the supine positions [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, once the decision is made to induce the patient for endotracheal intubation, the patient does not always need to be supine. 26,27 Thus, practitioners should be comfortable intubating patients in the head-up position. If this is the plan, it should be announced to the team.…”
Section: Achieving Better Airway Teamwork Outside the Operating Roommentioning
confidence: 99%
“…[31][32][33] Hemodynamics permitting, a sitting position can also ameliorate patient respiratory distress, reduce the risk of aspiration, and avoid complications associated with endotracheal intubation. 27 For patients with a nasogastric tube, airway intervention should be avoided until the stomach is emptied. If the nasogastric tube is not already present, placing one for this purpose should be considered.…”
Section: R: Reset Resistmentioning
confidence: 99%
“…Furthermore, as adjunctive strategies such as ramp positioning (12)(13)(14) and apneic oxygenation (15,16) have become increasingly recognized as potentially beneficial, a continuous training curriculum provides opportunities for evaluating trainees' knowledge of these techniques and reinforcing their incorporation into airway management.…”
Section: Discussionmentioning
confidence: 99%